The Influence of Transformational Leadership, Distributive Justice, and Intrinsic Motivation on Innovative Work Behaviour - Eni Anzarwati (JCOMENT (Journal of Community Empowerment), 2021)
This study aims to examine the influence of transformational leadership, distributive justice, and intrinsic motivation. The sampling method used in this study was non-probability sampling with purposive sampling technique. The population in this study were teachers of SMAN 1 Pangkalan Banteng and SMKN 1 Pangkalan Banteng. The number of samples used in this study amounted to 93 respondents who have worked for at least one year, and are permanent teachers at SMAN 1 Pangkalan Banteng and SMKN 1 Pangkalan Banteng. Data was collected through a survey method using a questionnaire that was distributed directly. The quantitative data analysis technique in this study uses multiple linear regression with the help of IBM SPSS 26 software. The results of this study prove that Transformational Leadership has a positive and significant effect on Innovation Work Behavior, Distributive Justice has no effect on Innovation Work Behavior, and Intrinsic Motivation has a positive effect and significant to Innovation Work Behavior. but together, Transformational Leadership, Distributive Justice, and Intrinsic Motivation have a positive and significant influence on Innovation Work Behavior.